Impact Load Identification with Uniform Noise Based on Forward-backward Splitting Algorithm - Gao, Wei; Zhang, Bochen (Journal of physics. Conference series, 2023)
In this paper, the forward-backward splitting method is introduced for the first time to solve the impact load identification problem under the condition of uniform noise in the field of structural dynamics. In the process of using this method to solve the problem of impact load identification, firstly, the load identification model is established. Then, the model is transformed into an optimization problem with infinite norm constraints by the maximum posterior estimation, and then the forward-backward splitting method is used to solve the optimization problem. The rationality and effectiveness of the forward and backward splitting method for load identification under uniform noise conditions in the field of structural dynamics are illustrated by numerical simulation examples.